Cognitive Resilience and Learning Motivation of Broken Home Children: A Study on Students of Madrasah Ibtidaiyah Al-Ikhlas Ancaran - Nengsih , Wida; Gumiandari, Septi (CV. Akademi Merdeka, 2025)
The phenomenon of Broken Home among elementary school students is a social and psychological problem that impacts learning motivation, emotional stability, character, and academic achievement. This study aims to analyze the relationship between incomplete family conditions and learning motivation, as well as the role of resilience, social support, and the school environment in maintaining children's academic achievement. This study aims to analyze 1) students' cognitive condition and learning motivation, 2) factors that affect cognitive resilience, 3) the role of PAI in supporting learning motivation 4) strategies based on Islamic values to strengthen students' cognitive resilience and learning motivation at MI Al Ikhlas Ancaran. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, in-depth interviews, and documentation of Broken Home family students, PAI teachers, and homeroom teachers. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing by paying attention to validity through triangulation of sources and methods. The results of the study show that 1) students with a Broken Home background generally have a relatively good level of cognitive resilience, so they are able to adapt to academic challenges, 2) students show quite effective abilities in managing emotional stress that arise due to various environmental and family factors, 3) the level of student learning motivation is in the medium to good category, which reflects the internal drive to continue to excel Even though they face an incomplete family condition. 4) Islamic values-based strategies are effective in strengthening cognitive resilience and learning motivation. Other findings show a positive relationship between cognitive resilience and learning motivation where the higher the resilience students have, the stronger their motivation to learn. The home environment, madrasah and peer relationships are one of the supporting factors in Shiwa's cognitive resilience in increasing learning motivation. The results of the study stated that students affected by Broken Home families can maintain learning motivation if they have strong cognitive resilience and receive support from a conducive school environment.